Rendering Differentials: Introjective Architecture In The Age Of The Digital - Bernath, Doreen (2013)
Abstract This paper begins by probing the ambivalent and frequently conflicting relation between “architecture” and “picture”. The polemic of forms and techniques of representation imposing its order upon the nature of architectural production is debated in relation to forces of technological transformations driven by more profound cultural imperatives. There had been a persistent divide between the projective and the pictorial in the discipline of architecture in Western tradition from C15th to late C20th. The divide is still evident at the time of the spread of digital technology in design practice since 1980s, when vector graphics took on the task of projective elaboration and raster graphics dealt with pictorial manipulation. However, by the turn of the C21st, a particular capability of digital inter-convertibility led to the incidental dissolution of the divide and the end of the projective dominance. Rendering technology returns the visualising process to the perception-based “image of substance”. And at the same time the experimentation of force-dependent animate form is hinged upon the ability of visualizise differential calculations rapidly. The final part speculates on growing tendencies of pictorial materialisation and effect engineering as part of a different model of architectural production which can be called “introjective”.  Resumen Este ensayo inicia investigando la relación ambivalente y conflictiva entre la “arquitectura” y la “pintura.” La controversia en las formas y las técnicas de representación, que imponen sus ordenes sobre la naturaleza de la producción arquitectónica, se discute en relación con las fuerzas de las transformaciones tecnológicas accionadas por imperativos culturales más profundos. En la tradición occidental de la disciplina de la arquitectura, del siglo XV al siglo XX, ha existido una persistente división entre lo proyectual y lo pictórico. La división es todavía evidente en el momento de la propagación de la tecnología digital en la práctica de diseño desde los ochentas, cuando los gráficos vectoriales se hicieron cargo de la elaboración proyectual, y los gráficos en raster lidiaron con la manipulación pictórica. Sin embargo, hacia inicios del siglo XXI, una capacidad particular de inter-convertibilidad digital condujo a la disolución incidental de la división y al fin de la preponderancia de lo proyectual. La tecnología del renderizado hace que el proceso de visualizar retorne a la percepción de la “imagen de una sustancia.” Y, al mismo tiempo, la experimentación en forma animada dependiente de fuerzas, está supeditada a la habilidad para visualizar cálculos diferenciales rápidamente. En el final del texto se especula sobre las crecientes tendencias en la materialización pictórica y en la ingeniería de efectos como parte de un modelo diferente de producción arquitectónica, al que puede llamarse “introyectivo.”